Dynamical behavior of martensite-austenite transitions: simulations and experiments - Laguna, Maria Fabiana (2013)
The dynamical behavior of the reverse martensitic transformation has been numerically simulated with an atomistic model and compared with experiments in Cu-Zn-Al alloys. Starting from different configurations of the martensitic variants (varying mainly their mean size), the transformation to austenite was studied as a function of the heating speed. Both, experimental and numerical results show that at low velocities there is no dependence of the transition temperatures, whereas at higher speeds they gradually increase. Simulations allow us to have an insight of the underlying processes during the transition to austenite. They also show that a heating speed independent transition can only be obtained when a microstructure of very small variants is present.